Effects of Whatsapp and Facebook on academic, professional and social lives of medical students and resident doctors of North India - Singhal, Shubha; Chawla, Shalini (International Journal Of Community Medicine And Public Health, 2019)
Background: Whatsapp and Facebook are the communication apps which facilitate the exchange of instant messages, pictures, videos and thus help in connecting the people with each other. Although it has brought many benefits, these benefits have come at a price. People spend more than usual hours on social networking and find it difficult to concentrate on their work and studies. This study was planned to assess the effects of Whatsapp and Facebook on academic, professional and social lives of medical students and resident doctors. Methods: The study was conducted on 480 medical students and 275 resident doctors. The data were collected with the help of a questionnaire designed for gathering the effects of Whatsapp and Facebook on academic, professional and social lives of medical students and resident doctors. Results: Majority of the participants (98.3%) used both Whatsapp and Facebook and spent 1-2 hours per day on Whatsapp and Facebook. Nearly 45% participants said that usage of Whatsapp and/ Facebook had a positive impact on their study performance. More than half of the participants (54.6%) agreed that Whatsapp and Facebook use affected their mood and reduces their interpersonal interaction with family and friends. Conclusions: Study concludes that Whatsapp and Facebook have positive impact in academic and professional lives of medical students and doctors. However, excessive use of social networking sites for recreational purposes has negative impact on their mental and social health.